Réponses

2014-02-03T12:33:43+01:00
A)(-5)+(+3)=-5+3=-2
b)(+8)-(+5)=8-5=3
c)(-2)-(-3)=-2+3=1
d)(+4)+(-7)=4-7=-3
e)(+6)-(-3)=6+3=9
f)(-7)-(-6)=-7+6=-1
g)(+6)+(-10)=6-10=-4
h)(-10)+(-3)=-10-3=-13
i)(-10)-(+11)=-10-11=-21
j)(+5)-(-2)=5+2=7
2014-02-03T12:59:24+01:00
Bonjour,
A= (-5) + (+3) = -2
B= (+8) - (+5) = 3
C= (-2) - (-3) = 1
D= (+4) + (-7) = -3
E= (+6) - (-3) = 9
F= (-7) - (-6) = -1
G= (+6) + (-10) = -4
H = (-10) + (-3) = -13
I = (-10) - (+11) = -21
J = (+5) - (-2) = 7
voila j'espère t'avoir aider